THE EFFECT OF DISCOUNT PRICES AND COMPETITIVENESS OF MOBILE INTERNET SERVICES IN IMPROVING CUSTOMER LOYALTY THROUGH THE SERVICES QUALITY OF TELECOMMUNICATION PROVIDER AS MODERATION VARIABLES IN THE COMMUNITIES IN MEDAN CITY - Hendra Jonathan Sibarani; Fenny Krisna (Asian Journal of Innovation and Entrepreneurship, 2018)
Telecommunication providers are internet service providers. The purpose of the research was carried out to increase the growth and even distribution of telecommunication network infrastructure development which could further reach and improve access to information for the Indonesian people more broadly. This research method uses a quantitative approach, a type of quantitative descriptive research with the nature of research that is explanatory. The population in this study were people in the city of Medan who came from the District of Medan - Petisah. Sampling used in this study using the Slovin formula so that the number of samples used in this study was 100 people. Sampling uses a non-probability sampling approach. The type of sampling chosen is accidental sampling with a type of qualified volunteer sample. Research data analysis method is descriptive statistical analysis and multiple regression analysis. The results obtained in this study are that discount prices, service competitiveness and service quality as a moderating variable simultaneously have a positive and significant effect in increasing customer loyalty in the community in Medan City but on service competitiveness variables have a negative value and no significant effect in improving customer loyalty. Moderation variables are proven to be able to influence discount prices, service competitiveness in increasing customer loyalty in the community in the city of Medan, with a coefficient of determination of 15%